Technical and Economic Aspects of Biomass Co-Firing in Coal-Fired Boilers - M. Dzikuć; K. Łasiński (International Journal of Applied Mechanics and Engineering, 2014)
The article presents the analysis of the potential of using biomass and coal co-firing in the Polish electro energetic system and shows the benefits resulting from an increase of biomass amount in electricity production in one of the largest Polish power stations. The paper discusses the most often used technologies for biomass co-firing and the potential of using biomass in electricity production in Poland. It also emphasises the fact that biomass co-firing allows a reduction of greenhouse gases emissions to the atmosphere and helps decrease consumption of energy resources. The article also emphasises the economic meaning of increasing the share of renewable energy resources in energy balance, including biomass, due to costs related to greenhouse gases emissions charges. Finally, conclusions from using biomass and coal co-firing in electricity production are presented